Control beliefs, aging and verbal memory self- efficacy in independent older adults - Feldberg, Carolina (2009)
Objective: In the present study it was be evaluated the incidence that control beliefs and memory self efficacy have on verbal memory tasks. Hypothesis: Control and memory self efficacy beliefs of older adults affect performance on memory tasks. Method: It was used a transversal ex post facto-comparison group design. The following instruments were selected: Rey Auditory Verbal Learnig Test and Logic Memory , from the Signoret Battery. The Self-Efficacy episodic memory and two questions where added to asses locus of control. There were assessed 200 senescent that reside in the Independent City of Buenos Aires. Discussion: From the values obtained in the statistical analysis made, it is possible to concluded with a certain margin of error, that control and verbal memory self efficacy on episodic memory performance beliefs in older adults, especially internal locus of control with the dimensions self efficacy level and strength, affect performance on memory tasks.